RELATIONSHIP BETWEEN MONEY POLITICS AND CORRUPTION: HOW THEY THREATEN NIRMILITARY DEFENSE - Andi Muhammad Alif Ranggong; Zainal Abidin Sahabuddin; Arifuddin Uksan (International Journal of Social Science, 2023)
The change to a democratic political system in Indonesia, which previously adhered to an authoritarian system, does not mean that the former authoritarian system previously disappeared easily and quickly. candidates for leaders who legalize all means to pave the way to occupy the palace seats. One of them is by using the practice of money politics. Money politics or also known as money politics, as the name suggests, is a political practice that uses encouragement and injections of funds to carry out its political agenda smoothly. Money politics comes in various forms, such as vote buying, vote brokers, and political corruption. Corruption that is rooted in the government will cause systematic losses which will end up causing huge losses to the people, especially the lower middle economic class. With many corruption cases that continue to grow, this will threaten the resilience of our country. The dowry of money politics can be in the form of basic food assistance, infrastructure improvements to the "dawn attack" that gives money directly to the community. With the increasing rate of corruption in this country, corruption is one of the weaknesses of Indonesia's defense.